(untitled) (Economic Journal of Nepal, 2018)
Home-stay is new model of tourism development in Nepal which provides an excellent opportunity to share, see and feel the diverse countryside lifestyle, local culture, and tradition. It promotes the rural economy through the promotion of rural tourism. The article aims to assess the economic contribution of home stay entity of Nepal, based on the descriptive and exploratory research design. Data were collected from the 8 homestays out of 45 listed in Nepal Tourism Board. 55 households were selected randomly from 8 home-stays from different locations from the hinterland of Kathmandu valley. The result based on statistics reflects the significant increase in income and expenditure of local people in study areas. It is found that majority of respondents have managed their household expenditure from the income from home-stay. The income status of homestays in study areas was found good. All home-stay operators have reported the increment in their savings and credit activities which directly contributes to the improvement in their economic status. However, it is also found that there need to improve the quality in home stays to increase the income of home-stay operators. The inequality pattern of male is more than women and have equal decision-making status.